Interparental conict from the perspective of children and sexual behavior of risk in dolescent in an Educational Institution of the Moras, Huanuco - Manrique de Lara Suárez, Digna (2018)
The objective of the study research was "To determine the relationship that exists between the conflict of paternal inner from children's perspective and the sexual risk behaviors in adolescents in a school in Las Moras, Huanuco, 2017. A descriptive, prospective and correlational study research was applied. The sample consisted of 133 adolescents and young people between 14 and 20 years old in whom the Conflict of Paternal Inner Scale was applied from the Children's Perspective (CPIS) and a questionnaire on risky sexual behaviors. The results showed higher percentages in: female sex 51.88%; ages of 16 and 17 years old with 29.3% and 22.6%; 63.2% entire family type, friends sexuality advice 30.8% and obtaining information from the school 59.4%; 10% have received domestic abuse; in risk behaviors, 26.3% started sexual intercourse, the age of onset was 16 years old; 51.4% with a single partner and the condom was the method of greatest use 48.6%; a risk of high sexual behavior 30.1%, an average perception of the conflict of paternal inner of 55.2%. It was concluded that there is a significant low relation between the study variables with a value of "Tau b" of Kendall of 0.238 and a value of p = 0.003.